Proposed Plan for Scaling of Climate-Smart Maps and Adaptation Plans (CS-MAP) for rice farming systems in Vietnam - Bong, Bui Ba (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This proposal on how to integrate the development and implementation of CS-MAP into the government’s policy framework was drafted by Former Vice Minister of Agriculture and Rural Development Dr. Bui Ba Bong. In the policy document, CS-MAP can be integrated into national and sectoral policies and plans, such as in the National Plan to adapt to climate change, Nationally Determined Contribution (NDC) to climate change mitigation in the agricultural sector, and in the national and regional agricultural restructuring plan for the period 2021-2025. At the local levels, CS-MAP, as a tool for climate change adaptation and disaster prevention, was proposed to be included in the socio-economic plan for the period 2021-2030, action plan to respond to climate change for the period 2021-2030, and agricultural land use planning (including rice land conversion), among others.